2011
DOI: 10.2495/wrm110091
|View full text |Cite
|
Sign up to set email alerts
|

Environmental optimization of tree-shaped water distribution networks

Abstract: In this paper two optimal tree-shaped networks for drinking water and irrigation are constructed by using the constructal approach coupled with the exergy destruction minimization method. It is shown that in the construction of treeshaped network for water distribution, the method of exergy destruction minimization is equivalent to minimizing mechanical irreversibility under a water quality constraint. For both energy consumption and the fluid quality degradation appearing in the network, this study offers new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Applying the tree-shaped fractal patterns to reflect WDN helps to find the best diameters scaling laws and optimal angles that minimise the total water head losses to the overall water residence time (Azoumah et al, 2012). Moreover, in the construction of WDN as a tree-shaped pattern, the method of exergy destruction minimisation is equivalent to minimising mechanical irreversibility under a water quality constraint (Bieupoude, et al, 2011).…”
Section: Applications Of Water Network Fractal Featuresmentioning
confidence: 99%
“…Applying the tree-shaped fractal patterns to reflect WDN helps to find the best diameters scaling laws and optimal angles that minimise the total water head losses to the overall water residence time (Azoumah et al, 2012). Moreover, in the construction of WDN as a tree-shaped pattern, the method of exergy destruction minimisation is equivalent to minimising mechanical irreversibility under a water quality constraint (Bieupoude, et al, 2011).…”
Section: Applications Of Water Network Fractal Featuresmentioning
confidence: 99%
“…For the specifi c case of pressure water distribution systems, two important phenomena are in competition: head losses leading to energy consumption and chemical losses causing water quality degradation, according to Kerneïs et al [5], showing that there is a trade-off to be found by design procedures. This is the concern of this paper which is an extended version of our recent works [6] in which thermodynamics of irreversible process is used [7] to describe the fl ow. This enabled to quantify the total exergy destruction of the system.…”
Section: Introductionmentioning
confidence: 99%
“…For the specifi c case of pressure water distribution systems, two important phenomena are in competition: head losses leading to energy consumption and chemical losses causing water quality degradation, according to Kerneïs et al [5], showing that there is a trade-off to be found by design procedures. This is the concern of this paper which is an extended version of our recent works [6] in which thermodynamics of irreversible process is used [7] to describe the fl ow. This enabled to quantify the total exergy destruction of the system.…”
Section: Introductionmentioning
confidence: 99%